ONLINE SHOPPING PERCEPTION AMONG MALAYSIAN PROFESSIONALS - Samsudin, Julianti; Ahmad, Shanusi (Journal of Technology Management and Business, 2014)
E-commerce has been emerging over the past two decades due to the advancement of Internet and information technology. The current trend of online shopping among Internet users are becoming more significant, especially among the young agers and professionals. This is due to convenience and beneficial perseption towards online shopping. The working professionals are identified as frequent online shoppers thus providing an opportunity to undestand their perception towards online shopping. The understanding on the perception on online buyers can provide marketer a guide to strategise their marketing advantage. Therefore, the objective of this study is to understand the online shopping demodraphy and to get meaningful insight on how they perceive online shopping which later shape their online shopping orientation. A sample of 1202 of polytechnic college’s academicians were asked for input and descriptive analysis was done to investigate factors that characterised their online shopping orientation. Based on the results, the study has shown several significant findings. It is found that there are three factors that have an effeect on online shopping orientation namely information search, religion commitment and religion concern. The findings consequently will stipulate the understanding on how professionals in Malaysia distinguish online shopping and what have modelled their orientation and perception towards e-commerce.